STUDENT'S CAREER PLANNING STABILIZATION WITH TRAIT AND FACTOR THEORY - Yufa Ficanysha; Daharnis; Mega Iswari (Literasi Nusantara, 2022)
The purpose of writing this scientific article is to find out how to strengthen students' career planning using trait and factor theory, where students find out the right career planning for them using trait and factor theory. Trait-Factor theory is a view that says that a person's personality can be described by identifying a number of traits, as far as the results of psychological testing measuring each of the personality dimensions are seen, trait and factor theory prioritizes student traits and personalities in matching the right choices for students. It is hoped that the student's career choice with the character and personality will be able to strengthen his career planning.